Correlation of Somatostatin Receptor 2 Expression, 68Ga-DOTATATE PET Scan and Octreotide Treatment in Thymic Epithelial Tumors - Roden, Anja C.; Rakshit, Sagar; Johnson, Geoffrey B.; Jenkins, Sarah M.; Mansfield, Aaron S. (Frontiers in Oncology, 2022)
Somatostatin receptor 2 (SSTR2) has been shown to be expressed in a subset of neuroendocrine tumors and carcinomas and plays a role in imaging studies and guiding therapy. Patients with tumors expressing SSTR2 may be successfully treated with somatostatin inhibitors or radiolabeled somatostatin analogues. We studied SSTR2 expression in TET and correlated it with 68Ga-DOTATATE PET/CT or 68Ga-DOTATATE PET/MR results and treatment outcome. An institutional database of TET was searched for thymoma, thymic carcinoma, and thymic neuroendocrine tumor (TNET) with available resection specimens. Cases were subtyped (2021 WHO classification) and staged (8th AJCC/UICC staging). A section was stained with anti-SSTR2 antibody (clone UMB1). Percent tumor cells with membranous staining was recorded if present in ≥1% of tumor cells. Medical records were searched for 68Ga-DOTATATE PET scans and treatment. Statistical analysis was performed. Eighty patients (1969-2021) with a median age of 61.3 years (range, 19.1-87.3) (37 males, 46.3%) had thymic carcinoma (N=33), TNET (N=7), or thymoma (N=40). SSTR2 expression was identified in 29 (of 80, 36.3%) TET including 2/2 (100%) small cell carcinomas, 2/5 (40.0%) atypical carcinoid tumors, 16/23 (69.6%) squamous cell carcinomas, 2/2 (100%) lymphoepithelial carcinomas, 1/1 (100%) adenosquamous carcinoma, and 6/40 (15.0%) thymomas. SSTR2 expression in ≥50% of tumor cells (vs 1-49%) was associated with younger age (p=0.023) and shorter recurrence/metastasis-free survival (p=0.007). 68Ga-DOTATATE PET scans (N=9) revealed a Krenning score of 3 in patients with atypical carcinoid tumor, small cell carcinoma, and squamous cell carcinoma (N=1 each) with SSTR2 expression in 95, 100, and 5% of tumor cells, respectively. Scans with Krenning scores of ≤2 (N=5) were seen in tumors with no SSTR2 expression in 80% of cases and a single atypical carcinoid tumor with SSTR2 expression in 10% of tumor cells. One scan resulted as “increased uptake” was in a patient with no SSTR2 expression. In conclusion, 68Ga-DOTATATE PET scans correlated with SSTR2 expression in TET in most patients and appeared to be useful to identify patients with TET who may be amenable to treatment with somatostatin analogues. Larger studies including more patients with 68Ga-DOTATATE PET scans are necessary to independently and prospectively validate our findings.